2014
DOI: 10.1007/978-94-017-9211-0_11
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between Mdm2, p53 and HIF1-α: Distinct Responses to Oxygen Stress and Implications for Tumour Hypoxia

Abstract: The E3 ubiquitin ligase Mdm2 regulates two transcription factors, p53 and HIF1α, which appear to be tailored towards different and specific roles within the cell, the DNA damage and hypoxia responses, respectively. However, evidence increasingly points towards the interplay between these factors being crucial for the regulation of cellular metabolism and survival in times of oxygen stress, which has particular relevance for tumour formation. Mdm2, p53 and HIF1α all respond to hypoxia, and intriguingly, have di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…The resulting decrease in TP53 restrains apoptosis and can favor angiogenesis by limiting angiostatic gene expression, such as Thrombospondin-1 (Dameron et al, 1994). It is worth noting that TP53 and HIF1-α can compete for binding to MDM2, which means that under hypoxia HIF1-α could restrain the capacity of MDM2 to inhibit TP53 (Robertson et al, 2014).…”
Section: Growth Factor Responsive Kinasesmentioning
confidence: 99%
“…The resulting decrease in TP53 restrains apoptosis and can favor angiogenesis by limiting angiostatic gene expression, such as Thrombospondin-1 (Dameron et al, 1994). It is worth noting that TP53 and HIF1-α can compete for binding to MDM2, which means that under hypoxia HIF1-α could restrain the capacity of MDM2 to inhibit TP53 (Robertson et al, 2014).…”
Section: Growth Factor Responsive Kinasesmentioning
confidence: 99%
“…Thus far it has been thought that inhibiting the MDM2/HIF-1alpha interaction would result in tumor cell death in hypoxia [147] but recently Joshi et al [84] found that MDM2 causes HIF-1alpha to be degraded during hypoxia so inhibiting the MDM2/HIF-1alpha interaction may actually result in tumor growth, not death. The role of p53 and its mutations can be regarded as well established in HNSCC, however its precise interrelationship with tumor hypoxia needs to be explored and clarified further.…”
Section: Vascular Endothelial Growth Factor (Vegf) and Tumor Hypoxiamentioning
confidence: 99%
“…Mdm2 can indeed regulate the activity of other transcription factors, such as HIF‐α and FoxO (11, 12). VEGF‐A is a well‐established target of HIF‐1α (21).…”
Section: Discussionmentioning
confidence: 99%
“…Mdm2 can sense endogenous and exogenous stresses through posttranslational modifications, such as site‐specific phosphorylation, that in turn control Mdm2 activity and recruitment of downstream targets (5, 10). For example, phosphorylation on Ser 166 in response to insulin‐like growth factor‐1 promotes degradation of p53 and HIF‐1α stabilization in tumor cells (11). Mdm2 also binds to FoxO proteins (12).…”
mentioning
confidence: 99%